EVALUASI PROGRAM PELATIHAN KEWIRAUSAHAAN OLEH DISNAKER KOTA PEKANBARU - Sitorus, Ergen; Tua, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research analyze about internship training program by Depertment of Labour in Pekanbaru, the purpose of this training have not been accomplished. From this problem, it is necessary to evaluate the implementation of entrepreneurship training program by Department of Labour in Pekanbaru. The purpose of this research is to evaluate the entrepreurial training especially the implementation of the program. This research is based on theory of William N Dunn that explains there are six evaluation criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. This study uses qualitative descriptive method and technique of data collection is done by interview, observation and documentation. Based on the result of interviews, researcher note that entrepreneurship training program by Depertment of Labour Pekanbaru still not reach the purpose of the program. It is ineffective as seen from the imperfect purpose and goal, the program also is inefficient seen from the time and man power needed is still not sufficient, the program also can not satisfy the need of the people, also the distribution of benefits to policy grup still uneven, and is still a lack of responsiveness to the problems that trainee faced, because many trainees are discontent to the program. The goals of the Program is good but still not properly implemented. This regulation must be repaired again to strengthen the basis of the program in the implementation of the program. This could happened because there are factors that affecting it such as, limited funds, limited human resource, and inadequation of facilities and infrastructure